2009
DOI: 10.1161/circep.108.829440
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ventricular Tachyarrhythmias by Intracardiac Repolarization Variability Analysis

Abstract: Background-Arrhythmic sudden cardiac death (SCD) is generally mediated by ventricular fibrillation (VF) or fast ventricular tachycardia (FVT). We studied the predictive value of temporal QT variability detected from various sources of cardiac electric signal: surface ECG, far-field (FF), and near-field (NF) intracardiac electrograms (EGMs) in patients with implantable cardioverter-defibrillators (ICDs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 26 publications
(18 reference statements)
3
57
0
Order By: Relevance
“…Pressure-volume (PV) loops were recorded in order to quantify the pacing-induced preload variability, with and without mechanical ventilation, simultaneously with LV MAP, in an additional set of 9 CAVB dogs (median 9 [7][8][9][10][11][12][13][14] weeks after AV-block). In the same experiment, the effect of SAC block by streptomycin on baseline BVR and arrhythmic response to dofetilide was tested; during pacing with alternating PQ, streptomycin was infused (40 mg/kg in 5 min i.v.…”
Section: Quantification Of Preload Variability and Effect Of Sac Blockmentioning
confidence: 99%
See 2 more Smart Citations
“…Pressure-volume (PV) loops were recorded in order to quantify the pacing-induced preload variability, with and without mechanical ventilation, simultaneously with LV MAP, in an additional set of 9 CAVB dogs (median 9 [7][8][9][10][11][12][13][14] weeks after AV-block). In the same experiment, the effect of SAC block by streptomycin on baseline BVR and arrhythmic response to dofetilide was tested; during pacing with alternating PQ, streptomycin was infused (40 mg/kg in 5 min i.v.…”
Section: Quantification Of Preload Variability and Effect Of Sac Blockmentioning
confidence: 99%
“…These results confirm the association between STVMAPD and proarrhythmia, and suggest involvement of the SAC in BVR in the CAVB dog. infusion: 27 vs. 4 [2][3][4][5][6][7][8][9][10][11][12][13] (P=0.07, Figure 6). However, this could not prevent an increase of STVMAPD, from 0.6±0.2 ms to 4.0±3.3 ms (P=0.006), and is similar to the value obtained in the group that received only dofetilide.…”
Section: Streptomycin Abolishes Response Of Bvr To Preload Variation mentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of alternate and non-alternate T wave oscillations increased immediately before the onset of ventricular tachyarrhythimia 9 and the QTVI is a useful method to identify unstable repolarization variability that MTWA fails to detect. Previous studies showed patients with ischemic or non-ischemic dilated cardiomyopathy had increased QTVI compared to control subjects 8,10,11 . The value of QTVI depended on severity of New York Heart Association (NYHA) functional class and was a predictor of total mortality, sudden cardiac death, and occurrence of ventricular tachyarrhythmias.…”
mentioning
confidence: 90%
“…SCD accounts for one out of every two deaths from cardiovascular diseases [2]. Therefore, development of the reliable predictor of VTA onset, namely the ventricular tachycardia (VT) and ventricular fibrillation (VF), is clinical important because the prediction provides opportunity to timely prevention of the negative consequences brought by VTA through early termination by implantable cardioverter defibrillator (ICD) [3].…”
Section: Introductionmentioning
confidence: 99%